PENGARUH KOMPETENSI DAN SISTEM AKUNTANSI TERHADAP KUALITAS PERTANGGUNGJAWABAN LAPORAN KEUANGAN PADA SATUAN KERJA DI LINGKUNGAN KANWIL KEMENTERIAN AGAMA PROVINSI RIAU - Hazrita, Fadilah; Rasuli, M.; Kamaliah, Kamaliah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2014)
This study aims to determine whether there are significantcompetence and Accounting System Institution (SAI) to the quality offinancial reporting responsibilities on the Kanwil Kementerian AgamaProvinsi Riau. Data obtained through census method by distributingquestionnaires to the work unit in the Religious Affairs Ministry RiauProvince. number of respondents were sent a questionnaire in thisstudy amounted to 66 people. Questionnaire developed and can beobtained further numbered 66. This study uses multiple linearregression. The results showed that competence does not affect thequality of financial reporting responsibilities, while the accountingsystem institution (SAI) affects the quality of financial reportingresponsibilities.